Anti-Hyperlipidemic Effect of Zinc complex of Betulinic acid in High Fat Diet- Induced Hyperlipidemia - Mehwish Tayyab; Adnan Jehangir; Farhana Ayub; Nimra Ijaz; Sameer Ahmed`; Attiya Munir (Journal of Rawalpindi Medical College)
Background: Hyperlipidemia is considered a modifiable risk factor for cardiovascular disease and atherosclerosis. Drugs of first choice, Statins, despite being well tolerable, are accompanied by many adverse effects. To tackle the shortcomings of standard drugs, there is dire demand to make an agent which equates to a better response. This study evaluated the anti-hyperlipidemic and comparative effects of Zinc complex of Betulinic acid (Zn+BA) with simvastatin (SIM), on high-fat diet-induced hyperlipidemia in rats, and the safety profile of the two treatments was also assessed.